Il colpo di stato in Grecia e la Giunta dei Colonnelli. Nodi e interpretazioni storiografiche / The Coup d'Etat in Greece and the Greek Colonels' Junta: Focal Points and Historical Interpretations - Cinzia Venturoli (Storicamente, 2012)
Many recent events have awakened international interest towards Greek politics and Greek economy. Greek contemporary history is quite unknown to our country. This is the reason why we chose to consider a fundamental period of Greek history, which is the seven years dictatorship of the colonels. We analyzed some important issues through a survey on Italian and Greek studies that were published during the dictatorship period and the following years. This text shows the results of our research.